Association of co-occurrence of gastrointestinal, sleep, and affective symptoms with Helicobacter pylori infection: a monocentric cross-sectional study in China - Zhang, ZhiHai; Ke, HongFei; ShangGuan, XiaoYan; Zhao, NengJiang; Hu, Xin; Li, Bo; Cai, MiaoNa; Chen, MeiQi; Liu, JiaHao; Wu, JieLong; Yang, ShuYu (Frontiers in Endocrinology, 2025)
BackgroundHelicobacter pylori (H. pylori) is a globally prevalent gastric bacterium implicated in gastrointestinal disease. Emerging evidence suggests it may also contribute to extra-gastric manifestations; however, its relationship with concurrent gastrointestinal, psychological, and sleep disturbances remains underexplored. This study investigated whether H. pylori infection is associated with a triad of gastrointestinal discomfort, sleep disturbance, and affective disorders.MethodsThis single-center cross-sectional study enrolled 969 adults at a H. pylori detection clinic (First Affiliated Hospital of Xiamen University) between June 2023 and June 2024. H. pylori infection status and severity were assessed using a 13C-urea breath test. Gastrointestinal symptoms, sleep disturbances, and affective disorders were evaluated with the Gastrointestinal Symptom Rating Scale (GSRS), Athens Insomnia Scale (AIS), and 4-item Patient Health Questionnaire (PHQ-4). Latent class analysis (LCA) was performed to identify distinct symptom phenotypes. Associations between infection severity and symptom clusters were examined using logistic regression adjusted for age, sex, and body mass index (BMI).ResultsIn terms of associated symptoms, 35.40% of participants reported gastrointestinal symptoms, 72.65% had sleep disturbances, and 61.09% experienced affective disorders. The prevalence of gastrointestinal symptoms, sleep disturbances, and affective disorders increased significantly with greater infection severity. LCA identified a “Positive Triad” phenotype (60.7% of the cohort), characterized by concurrent gastrointestinal, sleep, and emotional symptoms. Higher infection severity was independently associated with this combined symptom cluster after adjusting for age, sex, and BMI. The effect of H. pylori infection on risk of positive triad was significant among different gender, age group, and BMI group.ConclusionH. pylori infection was associated with concurrent gastrointestinal discomfort, sleep disturbance, and affective disorders. These findings suggest a unified symptom cluster attributable to H. pylori infection, extending its clinical impact beyond the gastric tract. Recognizing this multidimensional presentation could inform more comprehensive diagnostic and therapeutic strategies for affected patients.